2020
DOI: 10.1038/s41598-020-62516-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity at the invasion front of triple negative breast cancer cells

Abstract: Identifying better predictive and prognostic biomarkers for the diagnosis and treatment of triple negative breast cancer (TNBC) is complicated by tumor heterogeneity ranging from responses to therapy, mutational burden, and clonal evolution. To overcome the gap in our understanding of tumor heterogeneity, we hypothesized that isolating and studying the gene expression profile of invasive tumor cell subpopulations would be a crucial step towards achieving this goal. In this report, we utilized a fluidic device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This model was further tested in the patient-derived early passage triple negative breast cancer cell line VARI068 with robust EGFR expression. 40,41 VARI068 cells exhibit approximately 2-fold upregulation of Med25 relative to normal-like non-tumorigenic MCF10A cells. Treatment of VARI068 cells with NA blocks the Med25•ETV5 complex (Figure 4D).…”
Section: Resultsmentioning
confidence: 96%
“…This model was further tested in the patient-derived early passage triple negative breast cancer cell line VARI068 with robust EGFR expression. 40,41 VARI068 cells exhibit approximately 2-fold upregulation of Med25 relative to normal-like non-tumorigenic MCF10A cells. Treatment of VARI068 cells with NA blocks the Med25•ETV5 complex (Figure 4D).…”
Section: Resultsmentioning
confidence: 96%
“…In support of our observation, several reports have suggested that the KRT14 + cells have metastatic advantage in compared to KRT14 - cells in TNBC heterogeneous population and regulate the function of several genes involved in different stages of metastatic cascade. (Cheung et al, 2016; Granit et al, 2018; Yong et al, 2020). Further, KRT14 acts as a stem cell for the natural or injury induced bladder regeneration and typically lead the origin of bladder cancer (Papafotiou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…130-104-694) was used to enrich the digest for PCa human cells by depleting murine cell populations including fibroblasts, immune cells, and endothelial cells from the PDX digests. Previous studies have used this kit for similar applications 31 , 32 . Approximately 5 × 10 7 dissociated PDX cells were resuspended with 80 µL of cold separation buffer (0.5% BSA, 100 U/mL PenStrep in PBS) and 20 µL of Mouse Cell Depletion cocktail, and then incubated for 15 min at 4 °C, with occasional agitation.…”
Section: Methodsmentioning
confidence: 99%